Synonyms and their challenges for first-year students at the English Department, University of Languages and International Studies, Vietnam National University - Lý, Thanh Tú (ĐHNN, 2017)
This study is carried out to serve three major purposes: To conduct an investigation into different aspects of English synonyms.To address the issue of using some specific groups of synonyms of first year students in English Department, College of FLanguages,VietnamNational University.This is done by making the students to do some tests. Thentheirerrors in the tests are picked up and examined for causes and sources. To provide some recommendations for preventative and curative measures to help improve first year students‟ use of synonyms. This study is carried out to serve three major purposes: To conduct an investigation into different aspects of English synonyms.To address the issue of using some specific groups of synonyms of first year students in English Department, College of FLanguages,VietnamNational University.This is done by making the students to do some tests. Thentheirerrors in the tests are picked up and examined for causes and sources. To provide some recommendations for preventative and curative measures to help improve first year students‟ use of synonyms. This study is carried out to serve three major purposes: To conduct an investigation into different aspects of English synonyms.To address the issue of using some specific groups of synonyms of first year students in English Department, College of FLanguages,VietnamNational University.This is done by making the students to do some tests. Thentheirerrors in the tests are picked up and examined for causes and sources. To provide some recommendations for preventative and curative measures to help improve first year students‟ use of synonyms. This study is carried out to serve three major purposes: To conduct an investigation into different aspects of English synonyms.To address the issue of using some specific groups of synonyms of first year students in English Department, College of FLanguages,VietnamNational University.This is done by making the students to do some tests. Thentheirerrors in the tests are picked up and examined for causes and sources. To provide some recommendations for preventative and curative measures to help improve first year students‟ use of synonyms.